2016
DOI: 10.1111/mec.13597
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting cryptic species of the Litoditis marina complex (Nematoda) show differential resource use and have distinct microbiomes with high intraspecific variability

Abstract: Differences in resource use or in tolerances to abiotic conditions are often invoked as potential mechanisms underlying the sympatric distribution of cryptic species. Additionally, the microbiome can provide physiological adaptations of the host to environmental conditions. We determined the intra- and interspecific variability of the microbiomes of three cryptic nematode species of the Litoditis marina species complex that co-occur, but show differences in abiotic tolerances. Roche 454 pyrosequencing of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
119
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(127 citation statements)
references
References 51 publications
7
119
1
Order By: Relevance
“…In this study, for each of the main meiobenthic phyla (nematodes, arthropods, platyhelminthes and annelids) (Supplemental Material S1) there were some well-supported clades, particularly in the nematodes and nematodes, where OTUs assigned to the same genus, could potentially comprise species complexes. However without further molecular and taxonomic analysis, these would be difficult to define, but would be highly likely 40 .…”
Section: Discussionmentioning
confidence: 99%
“…In this study, for each of the main meiobenthic phyla (nematodes, arthropods, platyhelminthes and annelids) (Supplemental Material S1) there were some well-supported clades, particularly in the nematodes and nematodes, where OTUs assigned to the same genus, could potentially comprise species complexes. However without further molecular and taxonomic analysis, these would be difficult to define, but would be highly likely 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Most of these similar bacterial taxa are also found in the water and plants with which mosquitoes are in contact during immature and adult stages [38, 39]. A recent study on the Litoditis marina complex (Nematoda) described a divergent structure between the bacterial microbiota among three cryptic species [40]. The authors suggested a link between the microbiota, intrinsic physiological properties and trophic interactions specificities for each species.…”
Section: Discussionmentioning
confidence: 99%
“…Comparison with the aphelenchoidid nematodes associated with fig sycones (Kanzaki et al, 2014;Davies et al, 2015) is relevant here, where four genetically diverse groups of nematodes independently invaded sycones but have apparently converged morphologically due to the common selection pressures operating on them within the fruits (Kanzaki et al, 2014). Cryptic species of the marine bacterivore nematodes Litoditis marina have differences in their respective associated microbiomes, different feeding strategies and high inter-individual variability (Derycke et al, 2016).…”
Section: Cryptic Speciesmentioning
confidence: 99%